FLORAL TRAITS AND POLLINATION OF SPANISH CHERRY (Mimusops elengi Linn.) IN UNIVERSITI MALAYSIA TERENGGANU CAMPUS - SUKRI, HAIKAL HAZMI; GUNONG, FELICIA SYUPIE; IDIN, NAZURAH IDINNAZURAH; MOHAMED, NOR ZALIPAH (Universiti Malaysia Terengganu Journal of Undergraduate Research, 2021)
Some plants are self-compatible thus do not require pollinating agents for fertilisation of the ovule. Pollinating agents however are essential to promote cross-fertilisation, thus beneficial for the long-term survival of the plant species. In this study, we investigate the flower characteristics (flower size, colour, breeding system and nectar reward) and flower visitors of the Spanish cherry, Mimusops elengi, one of the most commonly planted ornamental trees in Universiti Malaysia Terengganu campus. Observations of flowers and the flower visitors were conducted between October 2016 and February 2017. The small sized flower, 19.88 + 1.70 mm (mean + SD) in height and 11.38 + 0.87 mm (mean + SD) in width; low volume with 11.90 + 5.55 μl (mean + SD) but with high sugar concentration with 26.57 + 3.72 % (mean + SD) nectar reward indicated insect pollination syndrome in this species. Xenogamy breeding system was determined for this species from the pollen-to-ovule ratio observation, which showed pollinating agents are required for cross-pollination to occur. Notes on the flower visitors revealed that two hymenopteran bee species, Xylocopa confusa and Heterotrigona itama as the pollinating agents of M. elengi. Not only these two species showed high visitation to the flowers, but they also land on the flowers to feed on the flower nectar, which could then potentially transfer the conspecific pollen grains on their bodies to the stigma for fertilisation of the flowers they visited.